Risk, Intermediate Input Prices and Missing Deflation During the Great Recession - Engin Kara; Ahmed Jamal Pirzada (Center for Economic Studies and ifo Institute (CESifo), 2015)
During the Great Recession, despite the large fall in output, inflation did not fall much. This is known as the missing deflation puzzle. In this paper, we develop and estimate a New Keynesian Dynamic Stochastic General Equilibrium model to provide an explanation for the puzzle. The new model allows for time-varying volatility in cross-sectional idiosyncratic uncertainty and ac-counts for the changes in intermediate goods prices. Our model can forecast the large fall in output and stable inflation during the Great Recession. We show that inflation did not fall much because intermediate goods prices were increasing during the Great Recession.
Keywords: E52; E58; 330; price mark-up shocks; Great Recession; inflation; DSGE; intermediate inputs